Между двух миров: Иван (Ованнес) Айвазовский (к 200-летию со дня рождения) - Алис Нерсисян (ՀՀ ԳԱԱ հրատ.)
Ազգությամբ հայ գեղանկարիչ Հովհաննես Այվազովսկին (1817–1900) XIX դարի ռուսական մշակույթի կարկառուն ներկայացուցիչներից էր: Հայերը և Հայաստանը մեծանուն նկարչի համար ներքին՝ հոգևոր կյանքի հիմքերն էին, մինչդեռ Ռուսաստանը և ռուսական մշակույթն արտաքին՝ ստեղծագործական կյանքի ձեռքբերումներն արտացոլող հայելիները: Armenian by origin painter Ivan (Hovhannes) Ayvazovsky (1817–1900) was one of the most eminent representatives of the 19th century Russian culture. Armenia and Armenians were the core of the prominent painter’s internal, spiritual self, while Russia and Russian culture were the mirrors reflecting the accomplishments of his successful outward life.
Keywords: Biography; Auxiliary Sciences of History; N Fine Arts; ND Painting